Global research hotspots and trends of acupuncture regulating neuroplasticity: a bibliometric analysis from 2005 to 2024 - Zhang, Qiaoli; Wen, Fayan; Qin, Wenxiu; Zhang, Xinghua; Zhu, Hai; Zhang, Fengfan (Frontiers in Neurology, 2025)
BackgroundAcupuncture has been widely used to relieve or cure various diseases. In this study, bibliometrics was used to comprehensively analyze the research focus and development trend of acupuncture regulating neuroplasticity, to provide new insights for future research.MethodIn this study, the Science Citation Index-Expanded database in the Web of Science Core Collection was used to retrieve and download the publications about acupuncture regulating neuroplasticity from 2005 to 2024. CiteSpace, VOSviewer, “Bibliometric” software package and Microsoft Excel were used for bibliometric analysis, and the number of publications, countries/regions, institutions, authors, journals, references and keywords were analyzed.ResultsA total of 264 publications, involving 905 institutions in 100 countries/regions. Overall, the publishing volume in the past 20 years has shown a steady upward trend. China has become the leading force in this research field, contributing the most high-quality publications. Guangzhou University of Chinese Medicine and Shanghai University of Traditional Chinese Medicine stand out as the most prolific institutions. Beijing University of Chinese Medicine and Harvard University have high academic influence. Among 1,586 authors, CZ Liu, XY Hua and JG Xu were identified as the most prolific authors. Frontiers in Neuroscience is the most published journal. In recent years, the mechanisms of acupuncture have attracted wide attention and become a hot topic.ConclusionWith the increasing research in this field, cooperation between different countries/regions, institutions and authors should be strengthened. AMPK, BDNF, brain-gut axis and brain-immune axis are the research hotspots and frontiers in this field. In the future, with the improvement of technical level, we should deepen the mechanism research, optimize clinical research and promote the standardization and individualization of acupuncture technology, which is expected to further reveal the scientific connotation of acupuncture regulation plasticity.